(untitled) - Cowan, Eugene W. (New York, 1968)
Contents: Chapter1: The Motion of charged particles; Chapter 2: The Electromagnetic Field; Chapter 3: Maxwell's Equations; Chapter 4: Electroagnetic Potentials
Keywords: Electromagnetism,Điện từ